Evaluating food contact surface and its influence on restaurant health ratings - Saeid Fallahizadeh; Majid Majlesi; Mohammad Reza Ghalehgolab; Mohammad Hassan Sadeghi; Mohammad Reza Zarei; Alireza R. Raygan Shirazi (Scientific Reports)
Abstract Controlling and maintaining the cleanliness of the working environment in restaurants is crucial. The aim of this study was to determine the level of contamination on food contact surfaces in restaurants. A total of 28 restaurants were surveyed, and 500 samples were taken from food contact surfaces that appeared clean and ready for use. The surfaces evaluated in this research included workers’ hands, tools and equipment, worktops, chopping boards, meat grinders, spoons and forks, plates, and kebab skewers. Each sample was collected using a swab on a designated 10 cm × 10 cm square area of the surface. The samples were then tested using a luminometer device to measure enzyme levels and identify bacterial contamination, helping to maintain health and control contamination. The unit of measurement for this device is RLU (Relative Light Unit). The results showed that the cleanliness of contact surfaces varied as follows: workers’ hands (46.43%), worktops (53.57%), kebab skewers (89.29%), plates (92.86%), meat grinders (76%), chopping boards (60.71%), tools and equipment (89.29%), and spoons and forks (96.43%). Regarding foodstuff contamination levels, the chopping board, worktop, and workers’ hands had the highest contamination with average RLU values of 1700.89, 1184.50, and 790.71, respectively. In contrast, plates had the lowest contamination, with an average RLU value of 46.68. Based on these findings, training restaurant staff in personal health, food safety, and regular hygiene practices, along with routine inspections based on guidelines from inspectors, will improve restaurant health standards and help reduce foodborne illnesses.